PROGRESSION OF CHRONIC LYMPHOCYTIC LEUKEMIA TO PROLYMPHOCYTIC LEUKEMIA: A RARE CASE REPORT - Amanatus Solikhhah; Nur Imma Fatimah Harahap (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Chronic lymphocytic leukemia, or CLL, is a chronic hematological malignancy marked by the overproduction of mature but nonfunctional lymphocytes. This condition is uncommon among Asian individuals. As a result, variations of this type of CLL are even less frequently observed. A CLL that presents with prolymphocytic progression is now recognized as a new illness in in the fifth edition of the World Health Organization classification. It is identified as a CD5+ non-mantle B-cell tumor featuring a minimum of 15% prolymphocytes in the bloodstream or bone marrow, and it partially supersedes the previous classification of B-cell prolymphocytic leukemia. Case Presentation: A 78-year-old woman experiencing increasing fatigue and difficulty breathing was brought to the emergency room and subsequently found to have Chronic lymphocytic leukemia. In this report, we highlight an uncommon instance of prolymphocytic leukemia advancement in a CLL patient within an exceptionally brief period of one week. Conclusion: Prolymphocytic transformation of CLL is a rare case with poor prognosis.This change was illustrated by the presence of undeveloped cells found in the peripheral blood, resembling prolymphocytes. The CLL patient unfortunately passed away shortly after being admitted to the hospital for a few days, which is atypical for traditional CLL patients who generally experience a longer duration of life. Thus, it is necessary to monitor the number of prolymphocyte in CLL patient as indicator of poorer transformation of chronic leukemia.